Peningkatan Kreativitas Seni Rupa Anak Usia 5-6 Tahun Melalui Kolase Daun - Fitria, Lutfiana; Siti Kurniasih (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Early childhood fine arts creativity at PAUD IT Tunas Harapan has not developed optimally, especially in fine arts creativity as evidenced by children still having difficulty in distinguishing colors, lack of children's creativity during learning activities and lack of children's imagination, and only fixated on the teacher's example. Based on these problems, researchers are interested in improving fine arts creativity in children using leaf collage media at PAUD IT Tunas Harapan Village Gedung Mulya Mesuji Regency. The formulation of the problem in this study is "How can the increase in children's fine arts creativity increase by using leaf collage media". The objectives to be achieved in this study are: "increasing children's fine arts creativity through leaf collage at PAUD IT Tunas Harapan Mesuji". This type of research is class action research conducted in 2 cycles; each cycle is carried out four times a meeting. The subject of this research is group B1 children at PUD IT Tunas Harapan, consisting of boys and girls. Data collection methods were carried out using two analyses including quantitative data analysis and qualitative data analysis. Based on class action research, it is known that the observation of children's development in each cycle is marked by the development of the percentage of indicators that increase children's fine arts creativity with learning activity assessment. In cycle I with an average value of 67% and cycle II reached an average value of 87% so that it increased by 20.0%. Thus, the researcher can conclude that the use of animated video media can improve children's fine arts creativity through leaf collage at PAUD IT Tunas Harapan.